ANALYSIS OF INTELLECTUAL DEVELOPMENT OF SCHOOLCHILDRENS (CLASS 1-11) ON SCHOOL NUMBER №1 LOCATED IN ANDIJAN CITY BASED ON THE ANFIMOVA TEST (Scientific journal of the Fergana State University, 2023)
In this study, an analysis of the level of intellectual development of schoolchildren #1 (classes 1-11) located in Andijan city of Andijan region was carried out using the Anfimova test. In this case, according to the Anfimova test in classes 2-11, the «Task execution accuracy coefficient» (A) (c.u.) in boys – 0,398- 0,952; in girls – 0,420-0,924; «Productivity of mental work performance» (P) (c.u.) in boys – 300,54-1495,54; in girls – 289,06-1446,99; «Stability of concentration level» (C) (c.u.) – 5,494-7,848; in girls – 4,391-7,761; «Volume of vision-related information» (Q) (bit) – 572,43-930,94; in girls – 520,64-921,86; in children «Speed of information processing» (V) (bit/sec.) – 1,492-3,303; in girls – 1,470-3,175. The results obtained can serve as a scientific basis for the development of territorial anthropo-physiological standards, as well as for the development of practical measures based on the strategy of the individual approach, taking into account the physiological indicators of the body in optimizing the level of physical and intellectual development of students in the educational process at school.